ANESTEZJOLOGIA I INTENSYWNA TERAPIAApplication of cerebral oximetry in adult cardiovascular surgery – management protocol - Kucewicz-Czech, Ewa; Urbańska, Ewa; Wolski, Piotr; Knapik, Piotr; Borkowski, Jarosław; Podwińska, Ewa (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Cerebral oximetry is a noninvasive technology that continuously monitors cerebral tissue oxygen saturation, which is sensitive index of global cerebral hypoperfusion. The INVOS is approved as a trend-only cerebral oximeter. There are 2 different forms of brain injury that may occur after cardiac surgery – neurological dysfunction (focal or global neurological injury) and neurocognitive dysfunction (postoperartive confusion, agitation, delirium). Patients who underwent all cardiac surgeries with optimized cerebral oxygen delivery demonstrated lower incidence of permanent stroke and cognitive disfunction. We present the intraoperative management protocol designed to maintain rSO 2 values at or above 80% of the preinduction baseline.